An unprecedented antioxidative isopimarane norditerpenoid from bivalve clam, Paphia malabarica with anti-cyclooxygenase and lipoxygenase potential - Minju Joy; Kajal Chakraborty (Taylor & Francis Group, 2017)
Context: The yellow-foot bivalve clam, Paphia malabarica Chemnitz (Veneridae) is distributed in the southwest coastal regions of India. The ethyl acetate-methanol extract of this species exhibited significant antioxidant and anti-inflammatory activities. Objectives: To purify and characterize the bioactive compound from P. malabarica along with in vitro assays. Materials and methods: The edible portion of P. malabarica was freeze dried (1.20 kg, yield 20.0%) and extracted with ethyl acetate and methanol (1:1 v/v, 500 mL ×3) by sonication (8 h). The antioxidant activity against DPPH/ABTS+ and anti-inflammatory potential against cyclooxygenase-1,2 (COX-1, 2)/5-lipoxygenase (5-LOX) enzymes were carried out with varying concentrations (0.25-2.00 mg/mL) to determine the IC50 values. The crude extract was chromatographically fractionated and the fraction showing greater potential was further fractionated to yield the pure compound, which was characterized by extensive NMR, IR and mass spectroscopic analyses. Results and discussion: The fractionation of crude extract of P. malabarica was followed by structural characterization of the new rearranged isopimarane derivative, 18 (4 → 14), 19 (4 → 8)-bis-abeo C19 norditerpenoid. The isopimarane derivative displayed comparable antioxidant activity with α-tocopherol (IC50 DPPH scavenging activity ∼0.6 mg/mL), whereas anti-inflammatory (anti-5-LOX) effect of the title compound was significantly greater (IC50 0.75 mg/mL) than ibuprofen (IC50 0.93 mg/mL). In addition, the greater selectivity index (anti-COX-1IC50/anti-COX-2IC50 0.85) explained the lesser side effects of the isopimarane norditerpenoid than the nonsteroidal anti-inflammatory drug-based therapies. Conclusions: The isopimarane derivative isolated from P. malabrica can be a natural substitute to commercial drugs in future.